The devil is in the detail : quantifying vocal variation in a complex, multi-levelled, and rapidly evolving display - Garland, Ellen C.; Rendell, Luke; Lilley, Matthew S.; Poole, M. Michael; Allen, Jenny; Noad, Michael J. (The Journal of the Acoustical Society of America, 2018)
E.C.G. was funded by a Royal Society Newton International Fellowship. L.R. was supported by the MASTS pooling initiative (The Marine Alliance for Science and Technology for Scotland) and their support is gratefully acknowledged. MASTS is funded by the Scottish Funding Council (Grant Reference No. HR09011) and contributing institutions. Some funding and logistical support was provided to M.M.P. by the National Oceanic Society (USA), Dolphin & Whale Watching Expeditions (French Polynesia), Vista Press (USA), and the International Fund for Animal Welfare (via the South Pacific Whale Research Consortium). Identifying and quantifying variation in vocalizations is fundamental to advancing our understanding of processes such as speciation, sexual selection, and cultural evolution. The song of the humpback whale (Megaptera novaeangliae) presents an extreme example of complexity and cultural evolution. It is a long, hierarchically structured vocal display that undergoes constant evolutionary change. Obtaining robust metrics to quantify song variation at multiple scales (from a sound through to population variation across the seascape) is a substantial challenge. Here, we present a method to quantify song similarity at multiple levels within the hierarchy. To incorporate the complexity of these multiple levels, the calculation of similarity is weighted by measurements of sound units (lower levels within the display) to bridge the gap in information between upper and lower levels. Results demonstrate that the inclusion of weighting provides a more realistic and robust representation of song similarity at multiple levels within the display. Our method permits robust quantification of cultural patterns and processes that will also contribute to the conservation management of endangered humpback whale populations, and is applicable to any hierarchically structured signal sequence. Peer reviewed